Keratocystic odontogenic tumour: A diagnostic dilemma? - Jyothirmayi Mandla; Satheesha Reddy Bandalore Hanumantha; Ramamurthy Thyganadoddy Kempegowda; Neenu Udayalal (Wolters Kluwer Medknow Publications, 2018)
The keratocystic odontogenic tumours (KCOTs) are known for their peculiar behaviour, varied origin, debated development, unique tendency to recur and disputed treatment modalities. It can occur anywhere in the jaw, but commonly seen in the posterior part of the mandible. Radiographically, KCOTs present as well-defined radiolucent lesions with smooth and usually corticated margins. They may be either multilocular or unilocular on radiography. We present the case of a 26-year-old man with KCOT associated with an impacted mandibular third molar. The cyst was initially diagnosed to be a dentigerous cyst based on the clinical and radiographic features. The histological examination of the specimen finally confirmed it to be a KCOT.